EXAMINING THE ROLE OF INDIAN BANKS IN MAINTAINING FINANCIAL STABILITY IN INDIAN AND ABROAD BANKING SYSTEM - Singh, Dinesh Pratap (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the critical role of Indian banks in maintaining financial stability within both domestic and international banking systems. It examines the mechanisms by which Indian banks contribute to economic stability, including risk management, regulatory compliance, and financial inclusion. The study also compares the performance of Indian banks with their international counterparts, identifying key strengths and areas for improvement. Through a combination of qualitative and quantitative analysis, this research provides insights into the evolving role of Indian banks in the global financial landscape and offers recommendations for enhancing their stability and resilience.